Παρατηρήσεις στους Άθλους του Ηρακλέους του Ιωάννη Πεδιασίμου - ΣΤΡΑΤΗΓΟΠΟΥΛΟΣ Δημοσθένης (Byzantina Symmeikta, 2020)
REMARKS ON HERCULES’ LABOURS OF JOHN PEDIASIMOS Hercules’ Labours were composed by John Pediasimos for educational purposes in a peculiar form comprising both prose and verse. The Hercules’ Labours had been among the most popular texts of school textbooks during the 14th, 15th, 16th centuries; the fact is well shown by the extensive number of manuscripts (39) transmitted. The complete “prose” collection consists of fourteen texts. The first is a metrical preface, i.e. a distich in Byzantine dodecasyllable. The second, a poetical work, is transmitted either as an exaposteilarion or as a poem composed in six political verses and it contains the list of the twelve Labours of the hero.The remaining twelve texts contain respectively eachone of the twelve well known Labours of the mythical hero. The aformentioned texts have already been published, but it would be worth publishing the interlinear comments and the analysis related to them contained in the manuscripts. The poetic form consists of thirteen texts: a monostich in Byzantine dodecasyllable which is the metrical title of the work and twelve poems written in same meter, one of each Labour of Hercules. The latter texts were treated up to now as one and single poem. Nevertheless, it would be better to handle them as twelve different and single poems.